Addressing Cybersecurity and Data Breach Regulations: A Global Perspective - Avinash Gaur (Innovative Research Thoughts, 2023)
The complex relationship between technology and data in today's increasingly digital environment has altered the trajectory of contemporary society. However, this transition to digital has spawned serious problems, the most pressing of which is cybersecurity and the persistent risk of data breaches. the worldwide framework of laws and policies concerning cybercrime and data breaches. provides insight into the myriad methods used by different nations and regions to protect confidential data, lessen vulnerability, and promote a safe online atmosphere. the ever-changing character of cyber threats and data breaches, with all the havoc they can wreak on individuals, businesses, and economies. the intricacies of the international regulatory environment, which lay bare a sophisticated web of rules and regulations designed to cope with these issues on a worldwide scale.